The Use of TTW (Think, Talk, Write) Strategy in Developing Student’s Writing English Narrative Text - Annisa Djibran; Karmila Machmud; Sri Agriyanti Mestari (Transbahasa, 2025)
The objective of this research is to find out whether Think-Talk-Write (TTW) strategy develop students’ writing skill in narrative text. To achieve the objectives, this research employed a quantitative experimental method using one group pre-test and post-test design. The population of this research was the ninth grade students of SMPN 1 Bulango Timur, consisting of 29 students. Data were collected through writing tests on narrative texts before and after treatment. The results show that the TTW strategy gave a positive effect on students’ writing skill. The mean score of the pre-test was 23.65, while the mean score of the post-test increased to 39.03. The statistical analysis used Wilcoxon Signed-Rank Test because the post-test data were not normally distributed. The result of the test showed a significance value of p < 0.001 and an effect size of -1.000, indicating a strong and significant improvement in students' writing ability after the treatment. The increase in scores proves that Think-Talk-Write strategy effectively enhances students’ understanding and ability in writing narrative texts. From the data above, it can be concluded that the use of Think-Talk-Write (TTW) strategy is effective in developing the students’ writing skills in narrative texts. It provides structured stages that encourage students to think critically, collaborate through discussion, and express ideas in written form.